DIGITAL TRANSFORMATION IN PUBLIC SERVICES: CHALLENGES AND OPPORTUNITIES - Mahaphan, Kanyavee (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the critical dimensions of Digital Transformation in the public sector, focusing on its role in enhancing service delivery and aligning administrative functions with 21st-century technological advancements and citizen expectations. Method: Employing a qualitative research design, the study utilizes situational analysis tools including SWOT analysis, PEST analysis, and Porter’s Five Forces Model. It also incorporates comparative case studies from multiple countries to examine readiness, implementation strategies, and contextual factors influencing digital adoption. Results: The findings reveal that while Digital Transformation fosters operational efficiency, citizen-centric services, and strategic planning capabilities, it simultaneously introduces multidimensional risks such as cybersecurity threats, institutional resistance, and regulatory gaps. The analysis also highlights varying levels of preparedness across national contexts, suggesting the need for tailored integration strategies. Novelty: The study contributes to existing literature by synthesizing strategic frameworks and empirical cases into a unified roadmap for public sector digitalization, emphasizing not only technological adoption but also governance, risk mitigation, and stakeholder alignment as critical success factors for sustainable digital transformation.